The Effect Of Digital Marketing On Consumer's Loyalty Of Ovo Application In Bengkulu City - Yolan Agung Pratama; Yudi Irawan Abi; Iswidana Utama Putra (Universitas Dehasen Bengkulu, 2026)
The rapid development of information technology in the digital era has brought significant changes in consumer behavior, particularly in the purchasing decision- making process. Digital marketing, as a marketing strategy, utilizes digital platforms and optimal service quality. This study aims to determine the effect of digital marketing on consumer’s loyalty to the OVO app in Bengkulu City. This research is a quantitative descriptive study. The data collection method used a questionnaire, with a sample of 80 respondents. The results of a simple linear regression test were Y = 15.201 + 1.102 The results of the digital marketing (X) test showed a t-test of 14.132 > t-table of 1.664 and a significance level of 0.000 <0.05. Therefore, the hypothesis Ha is accepted and Ho is rejected. This means that digital marketing (X) has a positive and significant effect on consumers’ loyalty to the OVO app in Bengkulu City.